Cytological study on Sertoli cells and their interactions with germ cells during annual reproductive cycle in turtle. Issue 12 (18th May 2016) - Ahmed, Nisar; Yufei, Huang; Yang, Ping; Muhammad Yasir, Waqas; Zhang, Qian; Liu, Tengfei; Hong, Chen; Lisi, Hu; Xiaoya, Chu; Chen, Qiusheng
Abstract: Sertoli cells (SCs) play a central role in the development of germ cells within functional testes and exhibit varying morphology during spermatogenesis. This present study investigated the seasonal morphological changes in SCs in the reproductive cycle of Pelodiscus sinensis by light microscopy, transmission electron microscopy (TEM), and immunohistochemistry. During hibernation period with the quiescent of spermatogenesis, several autophagosomes were observed inside the SCs, the processes of which retracted. In early spermatogenesis, when the germ cells started to proliferate, the SCs contained numerous lipid droplets instead of autophagosomes. In late spermatogenesis, the SCs processes became very thin and contacted several round/elongated spermatids in pockets. At this time, abundant endoplasmic reticulum and numerous mitochondria were present in the SCs. The organization of the tight junctions and the adherens junctions between the SCs and germ cells also changed during the reproductive cycle. Moreover, SCs were involved in the formation of cytoplasmic bridges, phagophores, and exosome secretions during spermatogenesis. Tubulobulbar complexes (TBC) were also developed by SCs around the nucleus of the spermatid at the time of spermiation. Strong, positive expression of vimentin was noted on the SCs during late spermatogenesis compared with the hibernation stage and the early stage of spermatogenesis. These data provide clear cytological evidence about the seasonal changes in SCs, corresponding with their different roles in germ cells within the Chinese soft‐shelled turtle Pelodiscus sinensis . Abstract : This is the first data provide clear cytological evidence about the seasonal changes in SCs, corresponding with their different roles in germ cells within the Chinese soft‐shelled turtle Pelodiscus sinensis .